2019
DOI: 10.1503/cjs.004818
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection following abdominal surgery: a prospective cohort study

Abstract: Background: Surgical site infection (SSI) is one of the most common complications of abdominal surgery and is associated with substantial discomfort, morbidity and cost. The goal of this study was to describe the incidence, bacteriology and risk factors associated with SSI in patients undergoing abdominal surgery. Methods: In this prospective cohort study, all patients aged 14 years or more undergoing abdominal surgery between Feb. 1 and July 31, 2016, at a single large academic hospital were included. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
161
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(192 citation statements)
references
References 25 publications
23
161
1
7
Order By: Relevance
“…were several folds higher while Escherichia coli was generally similar to those of the US and European hospitals, even after considering surgeryspecific data [5,8,9]. The high contribution of GNPs in the current study was consistent with several reports from Saudi Arabia [10][11][12] and developing countries [1], that showed contribution rates between 55 and 77%. This may be explained by inadequate hand hygiene practices [22] and high environmental burden of GNPs, that are usually Table 3.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…were several folds higher while Escherichia coli was generally similar to those of the US and European hospitals, even after considering surgeryspecific data [5,8,9]. The high contribution of GNPs in the current study was consistent with several reports from Saudi Arabia [10][11][12] and developing countries [1], that showed contribution rates between 55 and 77%. This may be explained by inadequate hand hygiene practices [22] and high environmental burden of GNPs, that are usually Table 3.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, this can be used as a justification for initiation and continuation of broad-spectrum antibiotics, leading to a vicious cycle of enhancing resistance. Consistent with current data, a local study showed that 77% of pathogens isolated from SSI after abdominal surgery were resistant to the prophylactic antibiotic given preoperatively [11].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…13 In Alkaaki et al study, A total of 337 patients were included. 14 Only 23% of cultured bacteria were sensitive to the prophylactic antibiotic given preoperatively.…”
Section: Surgical Site Infections Alter the Outcome Of Surgery;mentioning
confidence: 99%